Database System Development for the Care of Elders in the Community - JARAEPRAPAL, Urai; JINPON, Puangrat (Walailak Journal of Science and Technology (WJST), 2018)
This participatory action research aimed to develop a database system for the care of elders in the community, Pak Poon sub-district, Nakhon Si Thammarat, Thailand. The key informants were composed of public health officers, community leaders, representatives of the Local Administrative Organization, elders and their families, and lecturers and nursing students of Walailak University. Research instruments included interview questions, an elderly health assessment form, a developed elderly health database system as an experimental tool, and a usability evaluation form. Data collection was conducted by survey, interview, group discussion, and observation. Quantitative data analysis was conducted by frequency distribution and percentage; the validity and reliability of the questionnaire were confirmed with experts for Cronbach’s alpha. The qualitative data revealed content analysis. The results show that the database system consists of, elder health assessment, comprising general information, prior illness and treatment, functionality, mental health risk, risk for fall, and environment, the required features to support achievement of the goal for well-being, consistent with their life style, social capital, and local wisdom. In addition, the database could be used to reduce early risk factors to protect from chronic illness, injury, and decline in physical and psychosocial function. The reporting requirement comprised frequency distribution in terms of capital, problems, and need. Perception of the system and its effectiveness were evaluated using a questionnaire after participants had had an approximately one month period of experience of using the system. The responses to the questionnaire were positive about the system features and system process. From executives and health officers and elders using the database system, it has been improved, based on feedback continuum.